The Impact of Pancasila and Citizenship Education (PPKn) on the Character Education of Students at SMK PGRI 1 Cimahi - HENDRIAWAN, Erry; MARLINA, Rina; PANDIKAR, Ernandia; SOFYAN, Edy (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:This research is motivated by the low level of character education among students who recognize the importance of character education; therefore, the subject of Pancasila and Civics Education (PPKn), which is one of the subjects that includes lessons in understanding, living, and practicing values in life, is used as a reference for cultivating the values of character education in students, particularly in their love for their country. This study aimed to determine the impact of Pancasila and Citizenship Education (PPKn) on character education at SMK PGRI 1 Cimahi. Citizen knowledge, civic character, civic abilities, and patriotism character are examined by the researcher. The research method employed is a quantitative research method, and random sampling is the sampling technique. His investigation yielded a mean result of 51.7123, while the mean character education score for students was 41.9726. This study concludes that Pancasila and civic education (PPKn) have an impact on the character education of students at SMK PGRI 1 Cimahi.Methodology:This study employs a questionnaire methodology, wherein a set of questions is formulated and distributed to participants with the aim of eliciting their responses to these inquiries.Findings:The collection of variable measurements was conducted with a Likert scale through the suspension method. The participants in this study consisted of students enrolled in the eleventh grade at SMK PGRI 1 Cimahi.Implication:The sampling method is conducted using probability sampling, specifically employing a probability sample design. This approach ensures that sampling is grounded in the principle that all units within the population have an equal chance of being selected